2012
DOI: 10.1371/journal.pone.0049825
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Neurodegeneration in Wilson’s Disease Revealed by Spectral Domain Optical Coherence Tomography

Abstract: Background/ObjectiveIn addition to cirrhosis of the liver, Wilson’s disease leads to copper accumulation and widespread degeneration of the nervous system. Delayed visual evoked potentials (VEPs) suggest changes to the visual system and potential structural changes of the retina.MethodsWe used the latest generation of spectral domain optical coherence tomography to assess the retinal morphology of 42 patients with Wilson’s disease and 76 age- and sex-matched controls. We measured peripapillary retinal nerve fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 37 publications
(35 reference statements)
4
43
1
Order By: Relevance
“…Both manifestations may resolve with continued therapy [39] . Small fiber peripheral neuro pathy involving the corneal nerve plexus [40] , as well as neuronal degeneration involving the retina have also been described [41] , using novel techniques such as corneal confocal microscopy and spectral domain optical coherence tomography, respectively. Psychiatric abnormalities, which may be present before hepatic or neurological signs in up to one third of patients [42] , include decreased academic performance or personality changes, sexual exhibitionism, impulsiveness, labile mood, inappropriate behavior, depression, paranoia, and schizophrenia, leading also to suicide in a discrete number of cases [15,33,43,44] .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Both manifestations may resolve with continued therapy [39] . Small fiber peripheral neuro pathy involving the corneal nerve plexus [40] , as well as neuronal degeneration involving the retina have also been described [41] , using novel techniques such as corneal confocal microscopy and spectral domain optical coherence tomography, respectively. Psychiatric abnormalities, which may be present before hepatic or neurological signs in up to one third of patients [42] , include decreased academic performance or personality changes, sexual exhibitionism, impulsiveness, labile mood, inappropriate behavior, depression, paranoia, and schizophrenia, leading also to suicide in a discrete number of cases [15,33,43,44] .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Aside from the small number of patients and the same patients having no serial OCT, another limitation of our work is the incomparability of the peripapillary and macular findings as the macular retinal layers were automatically detected, whereas the peripapillary retinal layers were manually measured using composite layers as previously described. [38][39][40] However, given the large number of multiple comparisons, we were required to use a general estimation equation as a conservative statistical model. To strike a balance between the level of significance and our study results, we designated P values of 0.05-0.1 as marginally statistically significant.…”
Section: Retrograde Atrophy Of the Retinal Layers In The Macular Regimentioning
confidence: 99%
“…The essential requirement for copper and ATP7B for retinal structure integrity is underscored by reduced thickness of total macula as well as ganglion cell and inner plexiform layer in WD patients. Up to 50% of WD patients have abnormal visual evoked potentials (VEPs; Albrecht et al, 2012). Immunohistochemical studies of mouse and human retina identified the presence of ATP7A in the retinal pigment epithelium (RPE), outer plexiform layer (OPL), and ganglion cell layer (GCL) of the BALB/c mouse retina (Krajacic et al, 2006).…”
Section: Function and Regulation Of The Copper-atpases In Cns Cell Typesmentioning
confidence: 99%